2017
DOI: 10.18295/squmj.2016.17.02.015
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Multiple Myeloma Presenting with Diabetes Insipidus

Abstract: Multiple myeloma (MM) can present with involvement of the central nervous system in the form of nerve palsy, plasma cell masses or, rarely, with endocrinological effects due to involvement of the pituitary gland. Usually, in such cases, the disease has a rapid progression and poor prognosis. We report a 52-year-old man who was admitted to the Kolkata Medical College, Kolkata, India, in 2016 with a prolonged low-grade fever and hypernatremia. Shortly afterwards, the patient began to complain of increased urinar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Tahiliani et al described the case of a 40-year-old female who presented with left-sided hemiparesis, later found to have stage III extramedullary multiple myeloma with CNS involvement [12]. Paul et al reported a case of a 52-year-old male with prolonged low-grade fever, hypernatremia, polyuria, and drowsiness, eventually found to have multiple myeloma infiltration of the posterior pituitary, thus causing cranial diabetes insipidus [28]. Lastly, numerous cases with the diagnosis of multiple myeloma have presented as isolated cranial nerve palsies, specifically oculomotor nerve, trigeminal nerve, and abducens nerve [29][30][31].…”
Section: Neurological Diseasementioning
confidence: 99%
“…Tahiliani et al described the case of a 40-year-old female who presented with left-sided hemiparesis, later found to have stage III extramedullary multiple myeloma with CNS involvement [12]. Paul et al reported a case of a 52-year-old male with prolonged low-grade fever, hypernatremia, polyuria, and drowsiness, eventually found to have multiple myeloma infiltration of the posterior pituitary, thus causing cranial diabetes insipidus [28]. Lastly, numerous cases with the diagnosis of multiple myeloma have presented as isolated cranial nerve palsies, specifically oculomotor nerve, trigeminal nerve, and abducens nerve [29][30][31].…”
Section: Neurological Diseasementioning
confidence: 99%